Irish influence on medieval Welsh literature - Sims-Williams, Patrick (Oxford : Oxford University Press, 2010)
Patrick Sims-Williams provides an approach to some of the issues surrounding Irish literary influence on Wales, situating them in the context of the rest of medieval literature and international folklore.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: Welsh literature -- To 1550 -- History and criticism; Welsh literature -- Irish influences